Hybrid Composites Based On Kenaf, Jute, Fiberglass Woven Fabrics: Tensile And Impact Properties. (2018) - Nor, A.F.M.; Sultan, M.T.H.; Hamdan, A.; Azmi, A.M.R.; Jayakrisna, K.
Abstract: Recently, environment and sustainability issues have arisen which resulting in remarkable achievements for green technology in the field of material production. Pertaining to this research, food tray table that are used in in-flight galley service is currently facing an environmental issue in regard of the use of non-degradable resources as the main element in food tray table production. Hence, this research is attempting an effort to propose a newly developed material, which has the element of natural fiber in hybrid composites consist of jute (J), kenaf (K) and fiberglass (FG) for food tray table with less sustainability issues. This paper presents the results of an experimental study on the mechanical properties consist of tensile and low-velocity impact properties on hybrid composites. The aim of this research is to investigate the dynamic response of the hybrid composites under low velocity impact energy, as well as to analyze the experimental data for damage characterization from the tensile and impact testing. Hybrid composites with four different configurations (FG-K-J-K-FG, FG-K-K-K-FG, FG-J-J-J-FG, FG-J-K-J-FG) is fabricating for 5 layers in the first stage, subject to the tensile testing. Meanwhile in the second stage, the best two configurations out of the four are subjecting to low-velocity impact with circular steel impactor at various energy levels from 10J to 40J. The results show that the FG-J-J-J-FG and FG-J-K-J-FG configurations of the specimens possess 90% better mechanical properties compared to FG-K-J-K-FG and FG-K-K-K-FG configurations in hybrid composites. Meanwhile, FG-J-J-J-FG is showing the best configuration for the newly develop material in impact test. In conclusion, these hybrid composites are viable to extend into a newly develop material for further investigation.